Sebaran Disparitas Antar Daerah di Kabupaten Banyumas - Dede Prabowo Wiguna (Jurnal Ekonomi dan Studi Pembangunan, 2016)
This study aims to examine regional disparities in Banyumas. Feature disparities such as slums and congestion being targeted research. In addition, connectivity become an integral part of this research by looking at the disparity of road infrastructure network. The results of this study indicate that by Williamson Index disparities between regions is small. However, if comparing with the dynamic economic approach of the GDP - capita looks different and Banyumas looked disparity, which is based on data obtained that the highest achievements is owned by a large part in Purwokerto area. From geography to numbers cynclomatic approach looks balanced regional development in the area of Purwokerto. The density of this area is also very high which when done observation, local slums and congestion are only found in the Purwokerto area and not in other areas within the administrative area of Banyumas. This arises from the polarization of development in the eastern part of Banyumas.Keywords: Disparity, Economic Approach, Geography ApproachJEL Classification: F63, R11